2022
DOI: 10.3390/environments9070077
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Photocatalysis of Amoxicillin under Natural Conditions and High-Intensity Light: Fate, Transformation, and Mineralogical Impacts

Abstract: The β-Lactam antibiotic amoxicillin is among the most widely used antibiotics in human and veterinary medicine. Consequently, amoxicillin is abundant in natural waters and can undergo diverse abiotic reactions to form degradation compounds under environmental conditions. Yet, little is known about these decay pathways and mineralogical impacts on environmental amoxicillin degradation. The current study focuses on understanding the mineralogical influences of amoxicillin degradation under ecological conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The possible amoxicillin degradation products were determined by non-target analysis using the Q-TOF LC/MS technique. As said in a previous work [16], little is known about amoxicillin decomposition and its impact on the environment. Knowing the degradation and transformation pathways of emerging contaminants (ECs) is crucial for several reasons: (i) to assess the risk associated with ECs and their transformation products (TPs) when they reach the environment; (ii) to determine the toxicity of unknown derivatives and (iii) to study processes to promote the removal or the complete degradation of ECs to nonhazardous compounds [31][32][33].…”
Section: Identification Of Amoxicillin Degradation Productsmentioning
confidence: 95%
See 1 more Smart Citation
“…The possible amoxicillin degradation products were determined by non-target analysis using the Q-TOF LC/MS technique. As said in a previous work [16], little is known about amoxicillin decomposition and its impact on the environment. Knowing the degradation and transformation pathways of emerging contaminants (ECs) is crucial for several reasons: (i) to assess the risk associated with ECs and their transformation products (TPs) when they reach the environment; (ii) to determine the toxicity of unknown derivatives and (iii) to study processes to promote the removal or the complete degradation of ECs to nonhazardous compounds [31][32][33].…”
Section: Identification Of Amoxicillin Degradation Productsmentioning
confidence: 95%
“…Therefore, in this paper, an application of the photocatalytic oxidation process for the degradation of residual antibiotic amoxicillin as a model pollutant in accordance with the second Watch list [14] (Table 1) is presented. Amoxicillin is selected as a widely used penicillin-type antibiotic whose presence in the environment has been widely investigated; it is abundant in natural waters despite its rapid hydrolysis and abiotic transformations into various decomposition products (DPs) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed 84.12% degradation of amoxicillin after 240 min under optimum conditions of pH 9.5, catalyst dose of 1.5 g L −1 and initial concentration of amoxicillin of 17 mg L −1 under 240 min of solar irradiation due to a synergistic effect. In addition, several other studies have also been reported using TiO 2 , 157–159 and supported TiO 2 160 on the photocatalytic remediation of amoxicillin.…”
Section: Removal Of Pharmaceutical Components Using Different Photoca...mentioning
confidence: 99%
“…Hence, it is necessary to conduct a large amount of research on the treatment and removal of amoxicillin from wastewater using a variety of photocatalysts before discharging it into the natural aquatic environment. 149–216…”
Section: Removal Of Pharmaceutical Components Using Different Photoca...mentioning
confidence: 99%
“…This behavior could be due, first of all, to the presence of traces of water in commercial pharmaceutical preparations, which can initiate hydrolysis reactions of some functional groups, such as the NH 2 group, with the formation of the OH group. On the other hand, structural transformations can also take place under the influence of oxygen in the air and/or sunlight, which can cause decarboxylation and heterocycle closing processes, as can be seen from the characteristic IR fingerprints [ 168 , 169 ].…”
Section: Drug Stability and Analysismentioning
confidence: 99%